EFEKTIFITAS MULTIMEDIA INTERAKTIF BERBASIS GOOGLE SITE TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Muhammad Khammas Ainun Ni'am; Eko Handoyo; Tri Joko Raharjo; Sri Sumartiningsih; Agus Yuwono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In this digital era, technological developments are developing rapidly and all sectors, including education, must also follow developments in this digital era. Currently, education in Indonesia applies the Merdeka curriculum, in this curriculum the content of science and social studies learning is combined into one to become science learning content, the content of science learning in elementary schools is one of the most important lessons. The science and science learning content encourages students to be more active and have critical reasoning. However, in the field, researchers found problems related to the learning media used by teachers, which had an impact on low student learning outcomes. This research was conducted at SDN Ngadem because researchers found problems in learning science and science in class IV which caused students' grades in that class to be relatively low. This research uses a quantitative approach with an experimental type design. Specifically, using a pre-test and post-test design with one group. The sampling method used was purposive sampling. The aim of this research is to measure the effectiveness of using interactive multimedia based on Google Sites in science learning. The research results, which can be seen in Table 2, show that the post-test score (89.14) is higher than the pre-test score (66.72). The N-gain score obtained shows that the increase in student learning achievement is in the medium category, with an N-gain value of 67. The conclusion of this research is that interactive multimedia based on Google Sites has a positive influence on student learning outcomes in class IV of SDN Ngadem, and thus , it can be said that the use of interactive multimedia is effective in improving student learning outcomes.